2019
DOI: 10.1152/japplphysiol.01048.2018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV-1 gp120 and TAT-derived microvesicles on endothelial cell function

Abstract: The aims of this study were twofold. The first was to determine if human immunodeficiency virus (HIV)-1 glycoprotein (gp) 120 and transactivator of transcription (Tat) stimulate the release of endothelial microvesicles (EMVs). The second was to determine whether viral protein-induced EMVs are deleterious to endothelial cell function (inducing endothelial cell inflammation, oxidative stress, senescence and increasing apoptotic susceptibility). Human aortic endothelial cells (HAECs) were treated with recombinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Recent studies show that EMVs, identified as CD62E + , are significantly increased in patients with HIV infection treated with antiretroviral therapy when compared to controls [ 36 ]. Additionally, Hijmans et al showed that HIV-1 proteins are able to induce EMV release from endothelial cells and to promote endothelial senescence, inflammation and oxidative stress [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that EMVs, identified as CD62E + , are significantly increased in patients with HIV infection treated with antiretroviral therapy when compared to controls [ 36 ]. Additionally, Hijmans et al showed that HIV-1 proteins are able to induce EMV release from endothelial cells and to promote endothelial senescence, inflammation and oxidative stress [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCR efficiency of all primer assays was tested using a five-point standard curve with a range from 25 to 0.04 ng/reaction of pooled cDNA in triplicates. Expression of angiomiRs was relatively quantified (2 −∆∆Ct method) [57] using two distinct strategies. The expression of miR-199a-3p was very low and below the detection limit in 14% of samples, and thus, was excluded from the analysis.…”
Section: Rt-qpcr For Angiomir Expressionmentioning
confidence: 99%
“…Like the blebbing mechanism, firstly the cytoskeleton adjacent to the site of shedding on the plasma membrane is disassembled, then the phosphatidylserine is translocated to the outer leaflet causing the plasma membrane to bulge ( Cohen et al, 2020 ). Functional microvesicles are involved in several physiopathologic conditions, such as inflammation, oxidative stress, and senescence ( Hijmans et al, 19852019 ). These vesicles differ from exosomes not only in formation mechanism, but also in size and molecular markers.…”
Section: Introductionmentioning
confidence: 99%